Leveraging Social Protection Programs for Improved Nutrition : Summary of Evidence Prepared for the Global Forum on Nutrition-Sensitive Social Protection Programs, 2015 - Alderman, Harold (World Bank, Washington, DC, 2016)
The Global Forum on Nutrition-Sensitive Social Protection Programs, convened by SecureNutrition and the Russian Federation, brought together 150 donors, implementers, and country leaders to identify practical ways to link the nutrition and social protection agendas. This background paper served as a springboard for discussion at the Global Forum, and represents a synthesis of evidence from nearly 120 references with a heavy focus on program evaluations. This paper finds that social protection transfers tend to increase household budget devoted to food—often more than other income sources—and highlights evidence that transfers can change diet composition and quality.